Crises Management at University of Basra An Analytical& descriptive Study - علوان شذى احمد (Journal of Economics and Administrative Sciences, 2012)
It is an analytical study carried out at university of Basra using a sample included the dean ,assistants and managers of scientific dept. in the university for about(63)managers .The study aimed at discovering a model of crises management in the university.The researcher adopted the descriptive survey methodology.To achieve the objective of the study ,a questionnaire of (41)statements was developed covering five main variables like ,signal detection, prevention and preparedness, response, recovery and learning .The validity of the questionnaire was done by a group of referees .Its stability was determined by Cronbach,s Alfa .The questionnair,s stability coefficient was(0.82).Collected data was analyzed using several kinds of statistical methods namely means ,standards deviation , variance analysis, Mann-Whitney(u) and Kruskal-Wallis(x2) to test hypothesis ,the study reached to many finding ,one of them is the concern of the managers in the university for the therapeutic procedures through dealing with crisis and taking actions to discover the crisis in future and declining the impact of negative effects . In the light of the results of the study the researgher cited some recommendations.